2020
DOI: 10.3390/ijms22010156
|View full text |Cite
|
Sign up to set email alerts
|

Sounds Stimulation on In Vitro HL1 Cells: A Pilot Study and a Theoretical Physical Model

Abstract: Mechanical vibrations seem to affect the behaviour of different cell types and the functions of different organs. Pressure waves, including acoustic waves (sounds), could affect cytoskeletal molecules via coherent changes in their spatial organization and mechano-transduction signalling. We analyzed the sounds spectra and their fractal features. Cardiac muscle HL1 cells were exposed to different sounds, were stained for cytoskeletal markers (phalloidin, beta-actin, alpha-tubulin, alpha-actinin-1), and studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 112 publications
1
7
0
Order By: Relevance
“…2 would suggest. Based on other data 67 and on the evidence of our in-vitro study, 68 the RR could be due to a biophysical mechanism, that is the creation of a so-called “coherent state” in the organism with the establishment of a long-range correlation (molecular dipole synchronization) between the molecules immersed in an aqueous environment, 90 which could modify their spatial arrangement and their conformation. The greater transparency of the plasma after RR could be due not only to the change in concentration of solutes (that we measured in our works) but also to their different organization in space supported by a different alignment between aqueous molecules, 64 , 67 , 68 , 69 which allows the light-photons to pass without scattering.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…2 would suggest. Based on other data 67 and on the evidence of our in-vitro study, 68 the RR could be due to a biophysical mechanism, that is the creation of a so-called “coherent state” in the organism with the establishment of a long-range correlation (molecular dipole synchronization) between the molecules immersed in an aqueous environment, 90 which could modify their spatial arrangement and their conformation. The greater transparency of the plasma after RR could be due not only to the change in concentration of solutes (that we measured in our works) but also to their different organization in space supported by a different alignment between aqueous molecules, 64 , 67 , 68 , 69 which allows the light-photons to pass without scattering.…”
Section: Discussionmentioning
confidence: 81%
“…This modification may be related to some physical processes as well as biochemical quantitative variations of serum components (lipids 19 ) as detailed in. 64 , 67 The data on turbidity could reveal the emergence of a spatial order between the molecular plasmatic constituents after the RR (for more details about this biophysical issue please see our previous works 64 , 67 , 68 , 69 ). …”
Section: Methodsmentioning
confidence: 98%
“…Figure 1, shows that murine and human alpha-tubulin are 100% identical. Since such an identity extends to aromatic amino acids, it may be deduced that the information processing ability of murine tubulin is identical to that of human tubulin and, therefore, that the results described by Dal Lin et al (2021), may be extrapolated to humans.…”
Section: Study Of Sequences and Structures Of Alpha-tubulins And Tmc1mentioning
confidence: 97%
“…If microtubules respond to sound frequencies in the range for ultrasounds, recent observations seem to indicate that tubulin responds also to sounds in the range for audible since it was demonstrated that audible sound stimuli changed the average fractal dimension and lacunarity of alpha-tubulin in the cultured murine cardiac muscle cell line HL1 (Dal Lin et al 2021). Therefore, it may be hypothesized that audible sounds, just as ultrasounds, may affect mental states by acting on tubulin in the context of the microtubules of neurons.…”
mentioning
confidence: 99%
“…According to the definition of sound, it is a vibration that propagates as an acoustic wave through a transmission medium, such as a gas, liquid, or solid, and an acoustic wave is a mechanical wave that transmits energy through the movements of atoms and molecules. 1 A sound wave is typically investigated in terms of its pressure levels, frequencies, and interactions with the environment. This interaction can be labelled as diffraction, interference, reflection, a combination of these three, or even refraction when it involves many media.…”
Section: Introductionmentioning
confidence: 99%